Detection of foodborne viruses in ready-to-eat meat products and meat processing plants - Markantonis, Nikolas; Vasickova, Petra; Kubankova, Monika; Mikel, Pavel; Botsaris, George (My University, 2018)
Several studies have confirmed the presence of foodborne viruses in different food products throughout the world. There is accumulating data suggesting that the economic burden of foodborne viral infections is rising, making the understanding and monitoring of their prevalence a necessity, for the modern food industry. The objective of this study was to examine ready-to-eat meat products and environmental samples originated from meat processing plants in Cyprus, for four foodborne viruses: norovirus (NoV GGI, NoV GII), rotavirus, hepatitis A virus, and hepatitis E virus. A total of 48 swab samples and 42 different pork meat products from two plants were analyzed in parallel. The reverse transcription real-time polymerase chain reaction revealed two swab samples from the same plant positive for norovirus GGI. The detection of norovirus on a slicer machine and on the hands of a worker, suggest that foodborne viruses can be present in meat processing environments.
Keywords: Foodborne viruses; Meat products